Muslim Scholars and the Challenges of Social Media Da'wah: Cyberbullying in Perspective - Sule, Muhammad Maga; Musa, Salihi Ashiru (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2023)
The rapid development of internet technology has transformed how social media platforms are used worldwide for communication. This article focuses on Muslim scholars and the challenges of social media Da'wah focusing on cyberbullying of scholars on social media platforms. The most of the social media-based social interaction tools are user-generated, in contrast to traditional media. It enables the user to control the message's content, with or without restriction or regulation. Some Muslims have been lured to use social media in violation of rules laid down in accordance with fundamental Islamic teachings because of their freedom to sign up for an account on any website of their choice and the freedom it involves. Accordingly, this study has identified some of the behavior of cyberbullying against Muslim scholars on social media and provide solution according to the Islamic teachings. The paper adopted qualitative survey where Interviews were conducted with seasoned social users. Some of the findings of the study revealed that Muslim scholars faces challenge cyberbullying in the course of carrying out Da'wah on social media. The paper’s conclusion is that in order to create a more peaceful and safer digital environment, social media users should communicate with good morals and manners, especially on online forums.